Impacts of coordinative training on normal weight and overweight/obese children’s attentional performance - Gallotta, Maria Chiara; Emerenziani, Gian Pietro; Iazzoni, Sara; Meucci, Marco; Baldari, Carlo; Guidetti, Laura (Frontiers in Human Neuroscience, 2015)
This study investigated the efficacy of a physical activity (PA) program to improve the attention span in normal weight versus overweight/obese children. The study was designed as a cluster-randomized controlled intervention. One hundred fifty-seven normal weight and overweight/obese primary school children were randomly divided in three cohorts: Traditional PA, Coordinative PA and a Control group (not attending any PA). Before and after 5 months of intervention, children were administered the d2-R test of attention. Results showed that participants’ attentional performances were significantly affected by Time (pre vs post; P < 0.01) and by Time x Group interaction (traditional vs coordinative vs control; P < 0.001), revealing significant different effects of intervention/exercise modality on children’s attentional performance, independently of their weight status. These data suggest that a 5-month school-based PA intervention can improve the cognitive performance in children. Further, the Coordinative PA intervention resulted in the most significant improvement in children’s attention.